APLIKASI KONSELING SISWA BERBASIS WEB (Studi kasus : SMAN 41 Jakarta) - Kholifatul Husna, (2020)
Counseling Guidance is a program of counseling teachers in each school. Likewise also in State Senior High School 41 Jakarta. Lack of information data obtained by students after students do guidance (Guidance Results). And the lack of a record of supporting data storage to carry out this guidance. Both grades, student data, and track record results of the guidance. Regarding the recording of stored data values, student data and the results of student guidance above resulted in the queue to conduct guidance is quite complicated. Therefore it is necessary to build a counseling information system design so that it makes it easy for BK teachers to get recorded data on grades, student biodata and supporting aspects. And make it easier for students to submit guidance and obtain a record of the results of the guidance. To reduce the queue for submission of guidance. This Student Counseling Application is web-based using the PHP programming language and MYSQL data storage (PHP MYADMIN), the design of the system will be drawn using a Unified Modeling Language or UML diagram, using the waterfall approach methodology, and PIECES analysis methodology, the expectation of file management or Student counseling data makes student counseling / guidance effective and efficient and for students to conduct and obtain student counseling in the counseling teacher. Keywords: Counseling, Unified Modeling Language (UML), Waterfall Method, PIECES analysis method.